Comparison of two new methods for implementa BPSK modulator using FPGA - Hebibi Amar; Arres Bartil; Lahcene Ziet (Institute of Advanced Engineering and Science, 2020)
The design of electronic systems has become mainly dependent on FPGAs applications. This is due to the softness effectiveness progress by reconfigurable computing and reduced time to develop solutions for digital signal processing. In this article, we present the theoretical backgrounds of a BPSK modulation and hardware designs of the BPSK system, a firstly with the help of Matlab/Simulink reliant on the System Generator and a second with Xilinx ISE VERILOG Hardware Description Language. In order to show the differences between them, in terms of efficiency, duration of development and how many resources are used in FPGA. For the projected system, we have a tendency to aimed toward employing a moderately sized, low-value FPGA to implement the system. The Atlys development board by Digilent to configure develops, and run the system, based on a Xilinx Spartan-6 LX45 FPGA.